Human papillomaviruses in urological malignancies: a critical assessment - Tolstov, Yanis; Hadaschik, Boris; Pahernik, Sascha; Hohenfellner, Markus; Duensing, Stefan (Urologic oncology, 2014)
Objectives - Infection with human papillomaviruses (HPVs) is intimately associated with anogenital tract malignancies including cervical and vulvar cancer, a subset of oropharyngeal cancers and certain types of skin cancer. A number of urological tumors have likewise been suggested to be associated with high-risk HPV infection; however, many studies are hampered by a limited number of detection methods. The goal of this review article is to define a set of key criteria when implicating a virus in a human cancer and to apply these criteria to HPV infection in urological cancers. - Materials and methods - We performed a survey of the literature to corroborate the evidence to support a causal relationship between HPV infection and major urological malignancies. - Results - A number of previous reports have implicated HPVs in urological malignancies including penile, prostate, and bladder cancer. Most reports, however, rely only on a limited number of detection methods and frequently use contamination-prone polymerase chain reaction based methods. To firmly establish a link between a viral infection and a human malignancy, it is paramount that an array of techniques is employed and that the virus is ultimately traced by either direct visualization or, in the case of viral genome that has integrated into the host genome, detection of viral genes and gene products as well as functional cellular perturbations. In any case, seroepidemiological studies are likewise crucial to support the evidence. Such evidence for a role of HPV in urological malignancies based on currently available techniques is only present for penile squamous cell carcinomas. - Conclusions - An increasing number of immunocompromised patients as well as novel developments in patient care may change the spectrum of HPV-associated neoplasms. This is examplified by results demonstrating a role of HPVs in rare urothelial carcinomas with squamous differentiation in patients with neurogenic bladder. Hence, it is important to keep HPV infection in mind when confronted with unusual disease manifestations of the urogenital tract.
Available online 17 October 2013
Gesehen am 23.10.2020